Performance analysis and flow visualization in a round tube heat exchanger inserted with wavy V-ribs - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2017)
This article presents thermal performance analysis, flow visualization, and heat transfer characteristic in a round tube heat exchanger inserted with wavy V-rib. The novel design of the wavy V-rib not only allows mass production and simple installation in the heating system but also remains the thermal performance and the heat transfer rate as near as those of the V-baffle design. The numerical investigation with finite volume method is selected to study and describe the mechanisms in the test section. The effects of rib thickness, rib height, and flow direction are considered for the turbulent regime. The numerical results are reported in terms of flow structure and heat transfer behavior. The relationship of the Nusselt number, friction factor, and thermal enhancement factor with various parameters is also concluded. The numerical results reveal that the optimum thermal performance is detected for the wavy V-rib at b/D around 0.1–0.15, while the optimal t/D is around 0.15–0.20 when considered at the simplicity of the wavy V-rib production.
Keywords: Baffle; Heat transfer enhancement; Heat Transfer Mechanisms